Edukasi Anemia melalui Kelas Ibu Hamil Menggunakan Buku Saku Cegah Anemia pada Kehamilan sebagai Upaya Pencegahan Anemia pada Ibu Hamil: Anemia Education through Pregnant Women Class Using a Pocket Books to Prevent Anemia in Pregnancy as an Effort to Prevent Anemia in Pregnant Women - Arisani, Greiny; Wahyuni, Seri; Lucin, Yeni (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Anemia is one of the most frequent complications associated with pregnancy. Normal physiological changes in pregnancy affect hemoglobin (Hb) and there is a relative or absolute decrease in Hb concentration. Anemia adversely affects maternal and fetal well-being and is associated with increased fetal morbidity and mortality. Adverse perinatal outcomes includeintrauterine growth retardation (IUGR), prematurity and low birth weight are significant risks of death, especially in developing countries. This service to society is of a natureeducational persuasive by providing health education in the form of health education about anemia in pregnancy through classes for pregnant women using media in the form of a pocket book to prevent anemia in pregnancy. The characteristics of pregnant women who took part in this community service activity included an average age of 29.13 years, most of them had low and middle education, did not work, were multigravida and most were in the third trimester of pregnancy. The average knowledge score of pregnant women before receiving health education using a pocket book to prevent anemia in pregnancy was 56 and after the education was carried out there was an increase in the knowledge score of 86 so that the pocket book could be an alternative use of health education media to increase the knowledge of pregnant women.